Antioxidative and Photoprotective Activity of Pinus nigra, Pinus strobus and Pinus mugo - Daria Oshetkova; Adam Klimowicz (Applied Sciences)
Substances that delay the skin aging process have become very popular lately. Undoubtedly, this is influenced by all kinds of efforts to maintain a youthful appearance for as long as possible. Plant-derived antioxidants are a group of compounds that exhibit protective properties against the degenerative effects of oxidative stress on skin aging. Another important factor that protects skin against aging is photoprotective agents. The comparison of antioxidant and photoprotective activities seems to be interesting. The aim of this study was to evaluate the antioxidant properties of Pinus strobus, Pinus nigra, and Pinus mugo extracts using two frequently applied methods, i.e., DPPH and ABTS. Moreover, the polyphenol content was evaluated using Folin–Ciocalteu method. The correlation between the polyphenol content, antioxidant potential of the extracts, and sun protection factor in vitro was evaluated. Extracts were prepared using methanol, ethanol, isopropanol, and n-propanol in three concentrations: 40% (v/v), 70% (v/v), and undiluted. Ultrasound-assisted extraction, which is a type of green extraction technique, was applied for 15, 30, or 60 min. The highest antioxidant activity determined by the DPPH and ABTS methods was observed for Pinus mugo extracts in 40% ethanol and 40% methanol, respectively, both after 15 min extraction. The highest total polyphenol content was also found in Pinus mugo extracts. These activities were significantly higher than those of Pinus strobus and Pinus nigra. Similarly, the highest SPF values were also found for Pinus mugo extracts. Moreover, a strong correlation was observed between the antioxidant potential and SPF—the highest values were found for the correlation between the SPF and antioxidant activity determined using the ABTS method. Based on the obtained results, Pinus mugo could be suggested as a possible component for use in cosmetics.